In vitro development of Agaricus brasiliensis in media supplemented with different brans - Donini, Lorena Pastorini; Bernardi, Eduardo; Nascimento, José Soares do (Pesquisa Agropecuaria Brasileira, 2006)
The mushroom Agaricus brasiliensis is usually grown in potato-based or compost media. The objective of this work was to evaluate the in vitro development of the strain ABL 97/11 of A. brasiliensis grown in culture medium supplemented with brans of maize, wheat, rice and soybean, in different concentrations. Cultivation was performed under constant temperature of 28ºC. Diameter of the colony was evaluated daily and after six days of cultivation, mycelial mass was obtained. The addition of soybean or rice brans did not favor the development in vitro of A. brasiliensis. The largest averages of mycelial mass and growth rate are obtained in medium containing 20% of wheat bran. The medium containing 10% of maize corn presents the highest growth rate among the different media under the same bran concentration.